Kebijakan Non Penal terhadap Pelaku Tindak Pidana Perjudian Jenis Sabung Ayam dalam Wilayah Hukum Kepolisian Sektor Kota Baru - Hisbah Hisbah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Gambling is a social disease that threatens real or potential social norms so that it can threaten public order. The purpose of this study is to determine the criminal law policy in tackling the criminal act of cockfighting in the Kota Baru Sector Police Law Area at this time and in the future, to find out the applicable policies carried out by law enforcers to tackle the criminal act of cockfighting gambling in the Legal Territory. New City Sector Police. In this study the author uses empirical juridical research methods. The criminal law policy against cockfighting gambling in the Criminal Code of gambling has been regulated in Article 303 bis and the penal code is four years in prison. Which is gambling is a game that puts valuable objects or money for betting. This incident makes gambling a criminal offense because any play that is played using money for betting is called gambling. Meanwhile, for the future, namely reforming the Draft Criminal Code is a must because the government must respond to these developments by planning a regulation that can include and reduce crimes in the field of decency, especially the crime of gambling in the type of cockfighting. So, this kind of thing requires a partnership between law enforcers and community members in overcoming the criminal act of gambling in order to create a social situation that is safe and clean from gambling that is troubling the public. The policy of law enforcement carried out by law enforcement officials in an effort to combat the crime of cockfighting gambling in the New City Sector Police jurisdiction is carried out by pre-emptive efforts, namely by focusing on efforts with an appeal to perpetrators of cockfighting gambling so that they have awareness and not. carry out gambling again because it is likely to disturb the security and order of the surrounding community. Then with preventive measures for prevention as a basis for eradicating gambling crimes in the New City Sector Police Legal Territory. Furthermore, through repressive measures, which are actions taken directly to eradicate crime by taking action so that the perpetrator is deterred and does not repeat the crime again.